Gene Mining and Flavour Metabolism Analyses of Wickerhamomyces anomalus Y-1 Isolated From a Chinese Liquor Fermentation Starter - Shi, Xin; Wang, Xin; Hou, Xiaoge; Tian, Qing; Hui, Ming (Frontiers in Microbiology, 2022)
Luzhou-flavoured liquor is one of Chinese most popular distilled liquors. Hundreds of flavoured components have been detected from this liquor, with esters as its primary flavouring substance. Among these esters, ethyl hexanoate was the main component. As an essential functional microbe that produces ethyl hexanoate, yeast is an important functional microorganism that produces ethyl hexanoate. The synthesis of ethyl hexanoate in yeast mainly involves the lipase/esterase synthesis pathway, alcohol transferase pathway and alcohol dehydrogenase pathway. In this study, whole-genome sequencing of W. anomalus Y-1 isolated from a Chinese liquor fermentation starter, a fermented wheat starter containing brewing microorganisms, was carried out using the Illumina HiSeq X Ten platform. The sequence had a length of 15,127,803 bp with 34.56% GC content, encoding 7,024 CDS sequences, 69 tRNAs and 1 rRNA. Then, genome annotation was performed using three high-quality databases, namely, COG, KEGG and GO databases. The annotation results showed that the ko7019 pathway of gene 6,340 contained the Eht1p enzyme, which was considered a putative acyltransferase similar to Eeb1p and had 51.57% homology with two known medium-chain fatty acid ethyl ester synthases, namely, Eht1 and Eeb1. Ethyl hexanoate in W. anomalus was found to be synthesised through the alcohol acyltransferase pathway, while acyl-coenzyme A and alcohol were synthesised under the catalytic action of Eht1p. The results of this study are beneficial to the exploration of key genes of ester synthesis and provide reference for the improvement of liquor flavoured.